Optimalisasi Surat Izin Mengemudi Online Guna Mewujudkan Pelayanan Publik Yang Prima - Karina Elisabeth Octavia Marpaung (Indonesian Journal of Police Studies, 2021)
Korlantas Polri through the Satlantas Polrestabes Bandung made a service innovation called SIM Online to cut bureaucracy regarding the making of new SIMs and SIM extensions which the implementation has not shown as prime service. Research is conducted to determine the ability of personnel, efforts to optimize it, and the factors that influence it. Theories used are Innovation Diffusion Theory and Management Theory. The concept used is the concept of public service, the concept of SIM, and the concept of SIM Online. This research applied qualitative research methods. The scope of the study is the Satlantas Polrestabes Bandung SIM Online service, the focus of the research is online service, as well as the factors causing ineffective services. Data collection techniques used were interviews, observation, and study of documents, the data were processed in a descriptive manner. The results of the study found that the system, implementing competencies, number of implementers, and socialization regarding SIM Online did not meet service standards. There are 2 types of factors that affect internally and externally namely the supporting and inhibiting factors. From the supporting factors of the running of the service namely the leadership policy, a good work culture, the existence of reward and punishment, the existence of good socialization and the expectations of the community in public services. From the inhibiting factors namely the competence of human resources is not yet qualified, the lack of financial support from the police station, as well as the level of knowledge and ability of the technological community is still lacking. It is recommended that the government open up opportunities for personnel to take part in development education by increasing personnel quota, launching budgets regarding maintenance and care and building cooperation with more media agencies. Keywords: Optimization of services, Online SIM, causal factors